roster - International Women's Forum (Organization) (Washington, D.C. The Forum, 1994)
It consists of 52 groups of women's forum members around the globe, which is arranged alphabetically by country. Its main purpose is "to bring together women of significant and diverse achievements in order to facilitate communication among and the empowerment of women". The directory lists names, addresses, and contact number of corresponding officers, board delegates and each member.
Keywords: International Women's Forum (Organization) -- Directories